Analysis of Students' Core Skills at Grade XI of SMK N 1 Angkola Timur Towards British Council EnglishScore - Satrria SB Pohan; Rahmat Huda; Shoufi Nisma Dewi; Happy Sri Rezeki Purba; Devita Sari Harahap; Siti Rohmadhona; Dyah Supraba Lastari; Nasibah Awae (jurnalalfa, 2025)
This quantitative study sought to evaluate the English competence of grade XI software engineering students at SMK N 1 Angkola Timur and to compare their school-assessed grades with an internationally recognized norm. The research was motivated by the rising need for English proficiency in the global workforce and the possible subjectivity of internal school assessments. The main objectives were to assess the students' proficiency levels according to the Common European Framework of Reference for Languages (CEFR), analyze their distribution across these levels, and investigate the correlation between their report card grades and their British Council EnglishScore (BCES) results. The research comprised 16 students who participated in the BCES Core Skills assessment, evaluating grammar, vocabulary, reading, and listening abilities. The analysis employed descriptive statistics. The results indicated a substantial disparity: All students achieved scores at the foundational Pre-A1 (37.5%) and A1 (62.5%) levels, resulting in a mean BCES score of 122.06. Conversely, their average report card grade was 86.56, with some children attaining grades as high as 90 when assessed at the lowest Pre-A1 level. Significantly, no student attained the requisite minimum score to access the writing and speaking test modules, highlighting a profound inadequacy in fundamental skills. The report suggests that the school's internal grades are an unreliable measure of actual English competence and advocates for an immediate curriculum reform.